2021
DOI: 10.3390/su131910882
|View full text |Cite
|
Sign up to set email alerts
|

Can Rural Road Construction Promote the Sustainable Development of Regional Agriculture in China?

Abstract: The sustainable development of agriculture is significant in protecting natural resources, protecting the ecological environment, ensuring food security, and eliminating poverty. Rural road construction promotes the flow of labor and capital between urban and rural areas, and plays a vital role in agricultural production and rural revitalization. This study aims to analyze the effect of rural road construction on the sustainable development of regional agriculture in China. We select five-dimensional indexes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…They promote the transfer of people, goods, and information in rural areas. The construction of rural roads contributes to the transfer of labor and capital between urban and rural areas, and it plays an important role in agricultural production and rural revival and renewal [17,62].…”
Section: Choosing a Set Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…They promote the transfer of people, goods, and information in rural areas. The construction of rural roads contributes to the transfer of labor and capital between urban and rural areas, and it plays an important role in agricultural production and rural revival and renewal [17,62].…”
Section: Choosing a Set Of Variablesmentioning
confidence: 99%
“…Despite the fact that the main drivers of farmland abandonment and their spatial relationships have been extensively studied, most research relied on local and static variables. Analyses of spatial patterns revealed that farmland abandonment was strongly determined by spatial factors, in particular environmental and geological conditions, as well as socioeconomic factors [17,18]. At the same time, very few attempts have been made to describe agricultural land abandonment with a dynamic approach [19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the central and local governments have invested a lot in the construction of rural transportation infrastructure, such as airports, railways, and roads. It has been proved that the investment in transportation can facilitate the flow of labor and capital between regions and promote rural economic development [54,55]. In particular, rural road construction is considered to be an effective means of poverty alleviation [56].…”
Section: Land and Industrymentioning
confidence: 99%
“…Rural road networks play a vital role in the economic development of a nation. In the context of developing countries, rural roads are essential for the transportation of agricultural products, poverty alleviation and accessibility improvement to basic facilities such as markets, schools and health care services [1][2][3][4]. However, inadequate rural road infrastructure-poor road condition, lack of accessibility and connectivity-can thwart the socio-economic development process of rural communities.…”
Section: Introductionmentioning
confidence: 99%
“…However, inadequate rural road infrastructure-poor road condition, lack of accessibility and connectivity-can thwart the socio-economic development process of rural communities. The development of rural road networks, therefore, has become an all-important policy agenda for the developing world [2,4,5]. Many countries have implemented impressive rural road development programmes.…”
Section: Introductionmentioning
confidence: 99%